Pengaruh Efikasi Diri Terhadap Hasil Belajar Siswa Yang Dimediasi Oleh Disiplin Diri - Ifiana, Nur (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The success of the process of implementing teaching and learning activities can be measured by the learning outcomes achieved by students. Students's success in learning is influenced by two factors, namely external factors through self-discipline and internal factors namely self-efficacy. The external factor of self-discipline also acts as a mediator of self-efficacy with the learning outcomes of students at SMA Negeri 1 Driyorejo class XI IPS and XII IPS. This research uses a quantitative approach with a type of field research. The research population of students at SMA Negeri 1 Driyorejo class XI IPS and Data collection using questionnaires and data analysis using Moderated Regression Analysis (MRA) assisted by SPSS version 25 research software. The results of the research show that self-efficacy has a positive and significant effect on learning outcomes, self-efficacy has a positive and significant effect on self-discipline, self-discipline has a positive and significant effect on learning outcomes, and self-discipline has a positive and significant mediating effect on learning outcomes, which is clarified as a quasi moderator because the self-efficacy variable has a significant effect on learning outcome variables, the next test is that the self-discipline variable has a significant mediating effect on learning outcomes.